BIOLOGICAL ACTIVITY OF AQUEOUS AND ORGANIC EXTRACTS OF SEAWEEDS FROM CEARÁ STATE, BRAZIL - Torres, Márcia Rocha; Sousa, Alessandra de Paula Alves; Filho, Eduardo Augusto Torres da Silva; Pessoa, Cláudia; de Moraes, Maria Elisabete Amaral; de Moraes, Manoel Odorico; Lotufo, Letícia Veras Costa (Arquivos de Ciências do Mar, 2017)
The present study evaluated the biological activity of 12 marine macroalgae from Ceará State, Brazil. From the collected species 48 extracts (aqueous, dichloromethane, acetone and methanol extracts for each species) were obtained. The activity of extracts were rated at the following bioactivities: lethality in brine shrimp nauplii, inhibition of the development of sea urchin eggs, hemolytic activity on mice erythrocytes and inhibition of in vitro cellular proliferation on tumor cell lines using MTT assay. This study revealed that nine among the 12 tested species presented some activity in the applied assays, being that of the red algae Botryocladia occidentalis the most potent one The acetone extract obtained from B. occidentalis inhibited the growth of four out of five used tumor cell lines with an IC50 in the range of 5.0 to 24.5 μg/ml, possessed antimitotic activity on sea urchin eggs at concentrations up to 100 μg/ml, with no hemolylic activity and moderate toxicity to brine shrimp nauplii. Further studies are necessary for chemical characterization of the active principles and more extensive biological evaluation.